Proportion of Subclinical Hypothyroidism in Patients with Diabetes Mellitus - Hendarto, Hari; Premono, Laurentius Aswin; Akbar, Femmy Nurul; Harbuwono, Dante Saksono; Subekti, Imam; Setiati, Siti (International Journal of Human and Health Sciences (IJHHS), 2020)
Background:According to some recent studies, a connection exists between type 2 diabetes mellitus (T2DM) and the occurrence of subclinical hypothyroid (SCH).This purpose of this research was therefore, to determine the proportion of SCH in those diagnosed with T2DM. Materials and Methods: Data was obtained for this cross-sectional study by analyzing 278 patients suffering from T2DM for at least 1 year. The collected data include glycemic control (HbA1c) and thyroid hormone. Those with triiodothyronine (fT3), thyroxine (fT4), and TSH (≥4 μIU/ml) were suffered from SCH and examined with ultrasonographic (USG) for clinical screening of thyroid diseases. Results:Approximately 7.2% patients with T2DM were above 60 years with significant differences in number of men and women diagnosed with diabetes mellitus. There is also a significant correlation between HbA1c and SCH in T2DM. Among 20 subjects with SCH, USG thyroid suggested thyroiditis in 15 subjects. Conclusions:The prevalence of SCH among T2DM patients is high, therefore, all those with T2DM need to be examined for thyroid dysfunction. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 12-15